Burden of osteoarthritis in India and its states, 1990–2019: findings from the Global Burden of disease study 2019. Issue 8 (August 2022) - Singh, A.; Das, S.; Chopra, A.; Danda, D.; Paul, B.J.; March, L.; Mathew, A.J.; Shenoy, P.; Gotay, C.; Palmer, A.J.; Antony, B.
Summary: Objective: To describe the burden of osteoarthritis (OA) in India from 1990 to 2019. Design: Data from Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2019 were used. The burden of OA –knee OA, hip OA, hand OA, and other OA– was estimated for India and its states from 1990 to 2019 through a systematic analysis of prevalence, incidence, years lived with disability (YLD), and disability-adjusted life years (DALY) using methods reported in GBD 2019 study. Result: Around 23.46 million individuals in India had OA in 1990; this increased to 62.35 million in 2019. The age-standardised prevalence of OA increased from 4, 895 (95% uncertainty interval (UI):4, 420–5, 447) in 1990–5313 (95%UI:4, 799–5, 898) in 2019, per 100, 000 persons. Similarly, DALYs due to OA increased from 0.79 million (95%UI:0.40–1.55) to 2.12 million (95%UI:1.07–4.23); while age-standardised DALYs increased from 164 (95%UI:83–325) to 180 (95%UI:91–361) per 100, 000 persons from 1990 to 2019. OA was the 20 th most common cause of YLDs in India in 2019, accounting for 1.48% (95%UI:0.88–2.78) of all YLDs; increasing from 23rd most common cause in 1990 (1.25%(95%UI:0.74–2.34)). Knee OA was the most common form of OA, followed by hand OA. The prevalence, incidence, and DALYs for OA and knee OA were consistently higher in females than males. Conclusion: The burden and impact of OA in India are substantial and is increasing. Adopting suitable control and preventive community measures to reduce modifiable risk factors (obesity, injuries, occupational stress) are needed to reduce the current and future burden of OA in India.